(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2021)
Graphic representation plays an important role in the territorial development of a country. The power of images is widely exploited in all consumer–based societies because it is powerful in producing a manipulation of ideas with respect to places and it helps to attribute senses and meanings to them. Graphic representation based on stereotyped images, symbols and brands therefore affects areas on different geographical scales, thus involving their tourist, cultural, creative and social development. A central element to contribute to these developments is the debate on the creativity of a country’s representative images. The paper intends to address how this issue is tackled in Japan. Japan is a very inherent multifaceted country, and the image that Japan exhibits today finds its roots in a much deeper historical background. The art of the Japanese image manifests itself in the union and blending of its boundaries, in the wonder of the concept of mono no aware, kiwa, musubi, kata and kawaii. The aim of this article is therefore to narrate why the fascination of what appears in the images is the result of a deep cultural background, even though it deals with only a small part of the history of Japan, which would deserve a more complex and extensive treatment. Furthermore, the contribution aims to illustrate how the peculiarities and originality of images contribute to influence the tourist appeal of this country.